Establishment of the chloroplast genetic system in rice during early leaf development and at low temperatures - Kusumi, Kensuke; Iba, Koh (Frontiers in Plant Science, 2014)
Chloroplasts are the central nodes of the metabolic network in leaf cells of higher plants, and the conversion of proplastids into chloroplasts is tightly coupled to leaf development. During early leaf development, the structure and function of the chloroplasts differ greatly from those in a mature leaf, suggesting the existence of a stage-specific mechanism regulating chloroplast development during this period. Here, we discuss the identification of the genes affected in low temperature-conditional mutants of rice (Oryza sativa). These genes encode factors involved in chloroplast rRNA regulation (NUS1), and nucleotide metabolism in mitochondria, chloroplasts and cytosol (V2, V3, ST1). These genes are all preferentially expressed in the early leaf developmental stage P4, and depleting them causes altered chloroplast transcription and translation, and ultimately leaf chlorosis. Therefore, it is suggested that regulation of cellular nucleotide pools and nucleotide metabolism is indispensable for chloroplast development under low temperatures at this stage. This review summarizes the current understanding of these factors and discusses their roles in chloroplast biogenesis.